2020
DOI: 10.3389/fimmu.2020.00189
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Intra-Uterine Ureaplasma parvum Infection Induces Injury of the Enteric Nervous System in Ovine Fetuses

Abstract: Background: Chorioamnionitis, inflammation of the fetal membranes during pregnancy, is often caused by intra-amniotic (IA) infection with single or multiple microbes. Chorioamnionitis can be either acute or chronic and is associated with adverse postnatal outcomes of the intestine, including necrotizing enterocolitis (NEC). Neonates with NEC have structural and functional damage to the intestinal mucosa and the enteric nervous system (ENS), with loss of enteric neurons and glial cells. Yet, the impact of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
6
11
0
Order By: Relevance
“…Whether such an accelerated maturation is sufficient to fully compensate for the identified loss of neurons Table 2 Immune cells count in the mucosal layer Control (n = 6) 5 h LPS (n = 6) 12 h LPS (n = 7) 24 h LPS (n = 7) 2d LPS (n = 6) 4d LPS (n = 6) 8d LPS (n = 7) 15d LPS (n = 6) remains to be elucidated. These findings combined with the unaltered PGP9.5-positive and doublecortinpositive surface area after 2 and 7 days of IA LPS exposure in a previous study (Heymans et al 2020), show that the ENS changes found are time-dependent and may recover following prolonged intrauterine inflammation. Interestingly, in a previous study, a similar loss of mature neurons was observed after chronic IA exposure to UP, indicating that different inflammatory triggers can induce similar ENS damage (Heymans et al 2020).…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Whether such an accelerated maturation is sufficient to fully compensate for the identified loss of neurons Table 2 Immune cells count in the mucosal layer Control (n = 6) 5 h LPS (n = 6) 12 h LPS (n = 7) 24 h LPS (n = 7) 2d LPS (n = 6) 4d LPS (n = 6) 8d LPS (n = 7) 15d LPS (n = 6) remains to be elucidated. These findings combined with the unaltered PGP9.5-positive and doublecortinpositive surface area after 2 and 7 days of IA LPS exposure in a previous study (Heymans et al 2020), show that the ENS changes found are time-dependent and may recover following prolonged intrauterine inflammation. Interestingly, in a previous study, a similar loss of mature neurons was observed after chronic IA exposure to UP, indicating that different inflammatory triggers can induce similar ENS damage (Heymans et al 2020).…”
Section: Discussionsupporting
confidence: 70%
“…These findings combined with the unaltered PGP9.5-positive and doublecortinpositive surface area after 2 and 7 days of IA LPS exposure in a previous study (Heymans et al 2020), show that the ENS changes found are time-dependent and may recover following prolonged intrauterine inflammation. Interestingly, in a previous study, a similar loss of mature neurons was observed after chronic IA exposure to UP, indicating that different inflammatory triggers can induce similar ENS damage (Heymans et al 2020). Enteric glial cells are important for neuronal maintenance, survival, and function (De Giorgio et al 2012), and are capable of generating enteric neurons in response to injury (Joseph et al 2011;Laranjeira et al 2011).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations